2018
DOI: 10.1016/j.renene.2017.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Rural electrification and capacity expansion with an integrated modeling approach

Abstract: In developing countries, mini-grids are seen as an important option to improve electrification rates in rural areas. In order to be successful, mini-grids face issues of operation and sizing of generation capacities. Current studies on the optimal sizing of mini-grids do not include capacity expansion feedbacks regarding the operator's or investor's long-term economic performance on growth in electricity usage, e.g. gap between demand and supply impacting the operator's income. Using a System Dynamics model, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The literature suggests that the willingness of people to be connected, and to buy and own electrical household appliances, depends on their income. In their rural electrification model, Hartvigsson et al (Hartvigsson et al 2018) define the potential number of electrical connections as a function of different socio-economic parameters, including the average income of people. Lenz et al (Lenz et al 2017) state that the wealthier or more modern a household is, the more inclined it will be to get a connection.…”
Section: Referencementioning
confidence: 99%
“…The literature suggests that the willingness of people to be connected, and to buy and own electrical household appliances, depends on their income. In their rural electrification model, Hartvigsson et al (Hartvigsson et al 2018) define the potential number of electrical connections as a function of different socio-economic parameters, including the average income of people. Lenz et al (Lenz et al 2017) state that the wealthier or more modern a household is, the more inclined it will be to get a connection.…”
Section: Referencementioning
confidence: 99%
“…The effect of capacity expansion strategies on long-term economic performance for a rural mini-grid operator was investigated by Hartvigsson et al in [21]. The research proposed a linear bottom-up model, and used DER-CAM to implement the capacity investment model.…”
Section: The Role Of Optimization In Demand Side Management (Dsm) Of Dermentioning
confidence: 99%
“…Another barriers and challenges of solar panel projects are policy and regulation, financing, and infrastructure have also been identified Rathore et al, 2018. This study suggested that some government policies have an effective impact on overcome some identified barriers, and many research recommendations have been developed in India Shukla et al, 2018. As a part of the integrated energy planning, solar panel has an essential role in the energy self-sufficient program Hartvigsson et al, 2018. Many challenges to community-based energy initiatives in developing countries are identified in the literature, often concerning the long-term operation of Renewable energy technologies, and the overall sustainability of the projects Shaw et al, 2015. As in many regions, many renewable energy projects in Yogyakarta already experience problem during their 1 st years or even months of operation, arising from lack of a maintenance budget, task and responsibility allocation, and insufficient participation and capacity building Guerreiro and Botetzagias, 2017.…”
Section: Introductionmentioning
confidence: 97%